2000
DOI: 10.1007/pl00011439
|View full text |Cite
|
Sign up to set email alerts
|

Financial distress, bank debt restructurings, and layoffs

Abstract: We develop a model of a financially distressed firm to analyze the implications of a bank debt restructuring when the operational characteristics of the firm's project for the post-distress period are endogenously determined as part of the workout. We establish a formal link between the debt restructuring and operational actions such as employee layoffs, and show how these actions are affected by the firm's capital structure, the ordering of absolute priorities, and the allocation of control rights and residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…This subsection presents a simple labor market model that, within a standard partial equilibrium framework, serves to illustrate the idea that different liability regimes imply different real behavior among firms. The model, based on a representative firm with risk neutral owners, builds on Padilla and Requejo (2000). After choosing its legal form between a limited or unlimited liability status, our analysis starts by considering that the firm has access to a production technology which requires an investment of I > 0 to buy a certain level of capital stock for the period.…”
Section: Risk Attitude and Real Behavior In The Labor Marketmentioning
confidence: 99%
“…This subsection presents a simple labor market model that, within a standard partial equilibrium framework, serves to illustrate the idea that different liability regimes imply different real behavior among firms. The model, based on a representative firm with risk neutral owners, builds on Padilla and Requejo (2000). After choosing its legal form between a limited or unlimited liability status, our analysis starts by considering that the firm has access to a production technology which requires an investment of I > 0 to buy a certain level of capital stock for the period.…”
Section: Risk Attitude and Real Behavior In The Labor Marketmentioning
confidence: 99%
“…They found that these recoveries are not only due to the economic downturn but also financial constraints due to fire-sale. (Padilla & Requejo, 2000) Shows that debt restructuring process will trigger operational actions to make the firm more "focused'. It enables creditors to impose their views on the firm's future prospects and the result of a shift of control right and residual claims from shareholders to creditors which are value increasing and reduce the future distress.…”
mentioning
confidence: 99%